A value-centric decision making framework for maintenance services outsourcing - Toossi, Amir (Cranfield University, 2011)
The shift in mindset of decision makers, from maintenance being a “necessary evil” and “cost centre” to a “profit contributor” in manufacturing companies has driven outsourced maintenance suppliers to employ value-centric approaches in order to design more effective maintenance programs. A value assessment for maintenance outsourcing must facilitate the trade-off between cost-centric and value-centric approaches to enable the maintenance service providers to design more effective maintenance organizations. This assessment should also help the customers in a well informed decision making in outsourcing their maintenance function in order to add value to their businesses. Therefore the aim of this research is to develop a decision making framework for maintenance outsourcing based on the assessed customer-value of outsourced maintenance services. Cont/d.
Keywords: Maintenance Services; Outsourcing; Value dimension; In-tangibles; Multicriteria decision making